Inflation and output volatility under asymmetric incomplete information - Giacomo Carboni; Martin Ellison (European Central Bank (ECB), 2009)
The assumption of asymmetric and incomplete information in a standard New Keynesian model creates strong incentives for monetary policy transparency. We assume that the central bank has better information about its objectives than the private sector, and that the private sector has better information about shocks than the central bank. Transparency has the potential to trigger a virtuous circle in which all agents find it easier to make inferences and the economy is better stabilised. Our analysis improves upon existing work by endogenising the volatility of both output and inflation. Improved transparency most likely manifests itself in falling output volatility.
Keywords: E32; E37; E52; 330; Asymmetric information; Imperfect credibility; Signal extraction; Dynamisches Gleichgewicht; Geldpolitik; Zentralbank; Asymmetrische Information; Unvollkommene Information; Volatilität; Bruttoinlandsprodukt; Theorie